Optimizing Renewable Energy Integration in Weak Grids withUPQC Controller - R., Rajasree; D., Lakshmi; R., Karthickmanoj; Stalin, K.; M., Batumalay (INTI International University, 2024)
Integrating renewable energy into weak grids poses significant challenges, including voltage instability, power quality deterioration, and limited capacity to handle variable generation. This paper proposes a methodology to improve the Power Quality in the weak grid with renewable energy penetration using additional Unified Power Quality Conditioner (UPQC) Controller. Bird Swarm Optimization algorithm is implemented in the conventional scheme to minimize the oscillations in the voltage signals.The proposedcontrol system evaluates the switching signals for the UPQC while accounting for variations in the grid's strength, wind speed, load currents, and dc link voltage dynamics. The efficiency of the suggested strategy for improving the PQ performance of weak grid-connected renewable energy sources in the presence of nonlinear loads was demonstrated by simulations conducted in MATLAB and experimental research.